Staffing the principalship : finding, coaching, and mentoring school leaders - Lovely, Suzette, 1958- (Association for Supervision and Curriculum Development, 2004)
"Help Wanted" signs are springing up outside our schools. The shortage of school administrators isn't coming, it's here. To thwart the shortage and keep schools on the cutting edge, we must exercise diligence in cultivating, training, and inspiring a new generation of school leaders-especially for the principalship. Staffing the Principalship offers a structured, adaptable approach to finding high-quality principals and administrators in the ranks of teacher leaders and aspiring applicants. The author shares her professional experiences to explain proven strategies that can increase your district's applicant pool and build a strong cadre of candidates ready and able to tackle the demands of the principalship. This book helps you determine how best to . identify and cultivate candidates for the principalship, . support principals in their first years on the job, . help experienced principals grow, . keep good leaders, and . train current and future leaders to delegate and redistribute responsibilities and tasks. Now is the time to invest in public education by making administrator support and development a top priority in your school district. Securing dynamic principals who can prepare students for the challenges of tomorrow is essential for the success of every school